(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
STUDY OF PERCUTANEOUS ASPIRATION OR PIG TAIL DRAINAGE IN CASES OF LIVER ABSCESS. INTRODUCTION:Liver abscesses, both amoebic and pyogenic, continue to be an important cause of morbidity and mortality in tropical countries. India has the 2nd most burden of liver abscess amongst all other countries. The advances in radiology like ultrasonography (USG) and CT-scan resulted in introduction of radiological guided aspiration and drainage of intra-abdominal abscesses as many cases are refractory to medical therapy.AIMS AND OBJECTIVES:To evaluate: demographic profile, etiology, clinical presentation and its management.MATERIALS AND METHODS:Study size and period: 70 cases, May 2017-18 Study conducted at: V.S.G.H, Ahmedabad Needle aspiration Guidelines: abscess size >5 cm or>65ccvolume. Pig Tail Catheter drainage Guidelines: abscess size >8 cm or >120 cc volume.USG done: on Day 1, 3, 7, 30.Patients above 18yearsand willing for long follow-up were included in study.Regular follow up with USG on every visit of patient was done.RESULTS: The mean hospital stay of Percutaneous aspiration (2.8 days) was less as compared to pigtail drainage(4.6 days) and hence the patient compliance is more in aspiration. But for the complete resolution of abscess cavity especially for large abscesses pigtail drainage offers better advantage than percutaneous needle aspirations provided the cavity is adequately liquefied. CONCLUSION:Percutaneous needle aspiration is minimally invasive and readily acceptable but not useful in large abscess. And Pigtail catheter drainage of abscess under USG guidance is better, safe and effective in larger abscesses but required longer hospital stay. As there is no significant difference in cavity resolution rate, Both Procedures could be used with equal efficacy in properly selected cases.